(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1994)
In the Manang area (north Annapurna Range; Nepal Himalaya), the Permo-Carboniferous succession is 1000 to 1500 m thick. Crinoidal biocalcarenites (Tilicho Lake Fm.) pass upward to alternating black shales and sharp-based white quartzose sandstones (Thini Chu Group). Detailed stratigraphic analysis of this unit allowed us to recognize and establish 5 new formations and 8 new members. The Marsyandi Fm., of Visean age, records an increase of subarkosic terrigenous detritus during the initial stage of Neotethyan rifting, and is capped by two sequences "Syringotbyris beds") characterized by transgressive sandstones rich in Serpukhovian brachiopods. The overlying black shales with subordinate quartzarenites (Col Noir Shale) are followed in the more proximal Bangba section by diamictites yielding dolostone rock fragments, documenting the first advance of glacial ice on rift shoulders, actively uplifted since the Bashkirian-Moscovian (Bangba Fm.). Next, glaciomarine to transgressive shelfal deposits are enriched first in igneous detritus and then in arenaceous rock fragments (Braga Fm.). Mafic to felsic magmatism during the climax of rifting was thus followed by active erosion of sedimentary successions, probably around the Carboniferous/Permian boundary. A major Early Permian transgression, coinciding with ameliorating climates at the end of the Gondwana glaciation, was followed by mainly estuarine chert-bearing quartzose pebbly sandstones capped by richly bioclastic shelfal deposits (Puchenpra Fm.). This second major transgression, associated with quartzose sandstones documenting subdued rift reliefs, is dated as Bolorian at Bangba, as Murgabian-Midian at Col Noirand as Djulfian at Tilicho. The base of the condensed outer shelf/upper slope carbonates capping the Thini Chu Group ("topmost biocalcarenites") is also strongly heterochronous, being dated as Bolorian to Kubergandian-Murgabian at Bangba and as Djulfian-Dorashamian at Col Noir and Tilicho. Thermal subsidence associated with the opening of Neotethys thus began as early as the Early Permian.